Paediatric Obstructive Sleep Apnoea: Pathophysiology and the Role of Myofunctional Therapy - Yan Kiu Li (Pediatric Respirology and Critical Care Medicine)
The pathophysiology of obstructive sleep apnoea (OSA) is well studied in the adult population, but not in the paediatric population, although it can be generally classified into anatomical, functional, and pathological factors, with the most common aetiology being adenotonsillar hypertrophy and a reduced neuromuscular tone of the upper airway (UA) muscles. It is vital to understand the pathophysiology behind paediatric OSA, so that treatment can be optimized. Although the first-line treatment remains to be adenotonsillectomy (AT), this is not always effective, as indicated by the complex pathophysiology of OSA, leading to residual OSA post-AT. Myofunctional therapy (MFT), a newer non-invasive method focusing on re-educating, strengthening, and stimulating UA muscles, improves neuromuscular tone and prevents airway collapse, as supported by multiple randomized controlled trials (RCTs). Outcomes after 2 months to 2 years of therapy have also been positive, with children experiencing improved sleep quality, reduced emotional distress and mood swings, and reduced daytime problems, whereas polysomnogram (PSG) results revealed a clinically significant reduced apnoea–hypopnoea index post-therapy. Major limitations include poor compliance for active MFT and the short duration of the studies with small sample sizes. Given the high prevalence rates of childhood OSA, it is essential that more high-quality studies and RCTs are performed to assess the effectiveness of this treatment method, with a specific emphasis on its long-term impacts, risks, and optimal treatment duration.